Perampanel Increases Cortical EEG Fast Activity in Child and Adult Patients Affected by Epilepsy: A Quantitative EEG Study. (July 2021) - Liguori, Claudio; Spanetta, Matteo; Izzi, Francesca; Russo, Angelo; Guerra, Angelo; Mercuri, Nicola Biagio; Placidi, Fabio
Objective: Quantitative EEG (qEEG) is an established technique used as objective measure for evaluating the effect of antiseizure medications (ASMs) on EEG background activity and monitoring cognitive effects of ASMs. Perampanel (PER) has been associated with relatively more tolerable cognitive effects in patients with epilepsy. The primary aim of the present study was to verify the effect of PER as first add-on ASM on qEEG in child and adult patients affected by epilepsy. The secondary aim of this study was to verify the effectiveness of the drug as first add-on treatment in both child and adult patients with epilepsy. Methods: We collected data from 17 adults and 10 children treated with PER as first add-on treatment, who underwent qEEG analysis before starting PER and at 3-month follow-up under stable treatment. Results: PER resulted with significant effectiveness in reducing seizures in both children and adults. Considering qEEG analysis, we observed at follow-up the significant increase in beta1 and beta total bands both in children and adult patients. In particular, children showed the significant increase of beta band frequencies predominantly in the occipital regions, whereas adults showed a widespread increase of beta activity. Moreover, we documented in both child and adult patients the global reduction of delta bands activity. Conclusions: This qEEG study documented the relative increase of cortical EEG fast activity in both children and adult patients affected by epilepsy and treated by PER. This result may suggest a potential less negative impact of PER on cognition in patients affected by epilepsy, other than demonstrating effectiveness of the drug when used as first add-on treatment in both children and adult patients.